Pemanfaatan e-Form Surat Pemberitahuan Pajak Penghasilan Bagi Wirausaha dan UMKM di Desa Purworejo Kecamatan Negeri Katon Kabupaten Pesawaran - Syafis, Kamadie Sumanda; Putri, Lidya Ayuni; Ambya, Ambya; Russel, Edwin; Sudrajat, Sudrajat (Penerbit Goodwood, 2024)
Purpose: The purpose of this community service activity is to assist in the reporting of tax returns (SPT) using electronic forms (e-Forms) and to provide a comprehensive understanding of the community and business actors. It is expected to empower and enhance the understanding of annual tax reporting for residents and business actors in Purworejo Village, Negeri Katon District, and the Pesawaran Regency. Methodology: The implementation of this community service uses the Participatory Rural Appraisal (PRA) method, a technique that enables the community to participate in making real action plans and monitoring and evaluating policies that affect their lives. Results: Through the training and socialization organized in this community service, business actors in the village became more aware of their tax obligations. Consequently, they are more diligent in recording their business transactions and income, enabling them to complete the e-Form SPT more accurately. Limitation: The results of this research may be difficult to announce because conditions in Purworejo Village may differ significantly from other villages or areas, making it difficult to generalize the findings. Contribution: By using digital technology and e-Form SPT, MSMEs can be more effective in fulfilling their tax reporting obligations and managing their administration. This activity encourages MSMEs to adopt modern technology, increase tax compliance, and reduce administrative burden.